Peptide linked perylene bisimide and diketopyrrolopyrrole: design, synthesis and investigation of mechanofluorochromism. Issue 23 (17th October 2022) - Venkateswarlu, D.; Swetha, T.; Boddula, Rajamouli; Singh, Surya Prakash
Abstract : The synthesis of perylene diimide (PDI-PEP ) and diketopyrrolopyrrole (DPP-PEP ) derivatives which are substituted with a peptide linker in a core and wings manner (here DPP acts as the core moiety and the peptide linker works as the wings). Abstract : Herein, for the first time, we report the synthesis of perylenediimide (PDI-PEP ) and diketopyrrolopyrrole (DPP-PEP ) derivatives which are substituted with a peptide linker in a core and wings manner (here DPP acts as the core moiety and the peptide linker works as the wings). Both molecules showed intramolecular charge transfer: aggregation caused quenching (ACQ) and multi-colour mechanofluorochromism by adding various dopants. Upon doping with various coloured dopants, the molecules' PL emission spectra in the solid-state were found to be 634 nm (pinkish-red) and 720 nm (light brown) for PDI-PEP and DPP-PEP, respectively. Compared to emission in solution, the solid-state emission was shifted towards a higher wavelength by ∼94 nm and ∼150 nm for PDI-PEP and DPP-PEP, respectively. These results will provide insights into the multicolour mechanofluorochromism through molecular conformation and interactions.